KEHIDUPAN PEREMPUAN DESA ONI, KAJIAN NARATIF LIFE HISTORY WH DI DESA ONI KECAMATAN KUALIN KABUPATEN TIMOR TENGAH SELATAN - Lima, Stofiani Susana; Mardani, Ambara Saraswati; Toni, Ratu Sarina; Klau, Erni Raster (Education For All, 2023)
Abstract This study aims to increase the activity of students, and the use of conventional This study aims to determine the life of WH who lives the status of a widow in the family, this role has been carried out since 2019. Activities carried out by WH daily are gardening and doing side jobs, namely making various kinds of snacks from bananas, sweet potatoes, and cassava. This study uses psychological well-being and public pedagogy theories to examine WH life in Oni Village. This type of research is qualitative research using the Life history approach method. They are used to help researchers understand the deeper meaning of WH Life in Oni Village before widowhood until now a widow who has three children, who acts as the head of the family, and Mother Tumah Tangga. Data collection techniques use observation, interview, and documentation techniques. Data analysis techniques begin by examining all data collected from informants. The results of the study can be concluded that the life of WH in Oni Village as a widow is not only focused on work to earn a living and take care of children, but, WH was also chosen to be one of the members of the PKK in the field of government and the field of spirituality WH was chosen to be the head of the mothers. Amid WH's busy life of earning a living and taking care of children, WH also takes time to carry out tasks in the fields of government and spirituality.